PENGARUH SENAM ASMA TERHADAP PENINGKATAN FORCED EXPIRATORY IN 1 SECOND (FEV 1) PADA PENDERITA ASMA - Rahmaya Nova Handayani; Denny Agustiningsih; Achmad Djuneadi (Universitas Harapan Bangsa Purwokerto, 2014)
Asthma is a disorder such as chronic inflammation of the airways that causes hyperactivity of thebronchi to various stimuli which is characterized by symptoms of recurrent episodic form of wheezing , coughing , shortness of breath and tightness in the chest , especially at night or earlymorning are generally reversible either with or without treatment. Asthma fluctuated ( intermittent) means it can be quiet without symptoms , but can not interfere with the activities developed mildto severe symptoms can even cause death . One indication of obstruction in the respiratory tract isForced expiratory volume in 1 second ( FEV1 ) decreased . Forced expiratory volume in 1 secondis the amount of air that is expelled as soon as possible in the first second after taking the deepest breath. The purpose of this study was to determine the effect of asthma gymnastics to increasedFEV1 in patients with asthma . The design of this study is a quasi experimental study with pre-post study design -test group design . FEV1 measurements made at the beginning , middle and endof the treatment of asthma gymnastics performed 1 week 3 times in the morning with a sample of20 respondents . Gymnastics asthma conducted every Tuesday , Thursday and Saturday at 07.00 pm for 12 weeks . FEV1 measurements done using sprirometri brand